A mesoionic carbene complex of manganese in five oxidation states. Issue 41 (3rd May 2022) - Wittwer, Benjamin; Dickmann, Nicole; Berg, Stephan; Leitner, Daniel; Tesi, Lorenzo; Hunger, David; Gratzl, Raphael; van Slageren, Joris; Neuman, Nicolas I.; Munz, Dominik; Hohloch, Stephan
Abstract : A rare, high-valent manganese(iv ) mesoionic carbene complex is shown to be stable in five oxidation states, spanning a 3 Volt voltage range. Abstract : Reaction between a carbazole-based mesoionic carbene ligand and manganese(ii ) iodide results in the formation of a rare air-stable manganese(iv ) complex after aerobic workup. Cyclic voltammetry reveals the complex to be stable in five oxidation states. The electronic structure of all five oxidation states is elucidated chemically, spectroscopically (NMR, high-frequency EPR, UV-Vis, MCD), magnetically, and computationally (DFT, CASSCF).